An Investigation of the Relationship between Corporate Social Responsibility and Corporate Financial Performance in Egypt: The Mediating Role of Information Asymmetry - Nancy Mohamed; Ahmed Rashed (Journal of Accounting, Business and Management (JABM), 2021)
The aim of this paper is to investigate the impact of corporate social responsibility (CSR) on corporate financial performance (CFP) through information asymmetry (IA) as a mediator. The study involved the whole sectors in the listed companies on Egx100 excluding Financial sectors (banks and financial services) from 2013-2017 using smart PLS (Partial Least Square). CSR is measured using CSR index, while Share turnover ratio is used to measure IA. CFP is divided into three indicators: ROA, ROE and ROS. The Structural model assessment reveals that CSR has a positive and significant effect on CFP. This means that those listed companies engaged in CSR activities achieved better financial performance than non- CRS companies. The CSR proved to have a negative and significant effect on the IA. This shows that CSR activities lead to decreased IA. Finally, this research found that CSR activities will improve CFP through IA.